1971
DOI: 10.1002/macp.1971.021430119
|View full text |Cite
|
Sign up to set email alerts
|

A study of some properties of aromatic imides

Abstract: The melting point, solubility and infrared spectra of a number of aromatic imides, mainly disubstituted N.N'-diphenylpyromellitimides, have been determined. The variation in properties observed could be explained satisfactorily by making certain assumptions about the planarity, polarisation and intermolecular interactions of the compounds. ZUSAMMENFASSUNG:Schmelzpunkt, Loslichkeit und Infrarot-Spektren mehrerer aromatischer Imide, hauptsachlich zweifach substituierter N.N'-Diphenylpyromellitimide, wurden gemes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(97 citation statements)
references
References 2 publications
3
93
0
1
Order By: Relevance
“…Studies of low molecular weight model imides supported this assumption (1 ), and spectroscopic examination of a series of polyimides indicated the presence of a low energy transition which was dependent upon the ionization potential of the diamine segment in the polymer backbone (2,3). One of the more interesting ramifications of this work has been the use of the charge transfer complex hypothesis to explain and predict structureproperty relationships of polyimides (4,5).…”
Section: Introductionmentioning
confidence: 61%
“…Studies of low molecular weight model imides supported this assumption (1 ), and spectroscopic examination of a series of polyimides indicated the presence of a low energy transition which was dependent upon the ionization potential of the diamine segment in the polymer backbone (2,3). One of the more interesting ramifications of this work has been the use of the charge transfer complex hypothesis to explain and predict structureproperty relationships of polyimides (4,5).…”
Section: Introductionmentioning
confidence: 61%
“…The 1783 cm" 1 absorbance, which possesses a transition moment vector parallel to the imide plane, is the symmetrical stretching band of the carbonyl groups (in-phase). In addition, it has a higher intensity compared with the intensity of the 1727 cm" 1 absorbance which is the asymmetrical stretching band of the carbonyl groups (out-of-phase) (24). Indeed, for many aromatic polyimides, we have found that the ratio of the intensities of these two bands is an accurate measure of the structural anisotropy in the thin films.…”
Section: Bis(trifluorome%l)-44'-diaminobiphenyl (Pfmb) Diamine (Bpdamentioning
confidence: 86%
“…By the surface analysis, no appreciable photochemical reaction of PI was observed on the surface by light; the optical switching might be due mainly to photophysical changes of the PI surface. [12][13][14][15] However, further works are necessary to understand fully this phenomenon. The optical switching of the NLC cell with photosensitive PIs as alignment layers is a driving method of NLC, which is applicable to optical switching devices of NLCs.…”
Section: Lee-soon Parkmentioning
confidence: 99%